Tabayyun-Based Digital Scaffolding for Young Children’s Responses to Aggressive Digital Content: A Qualitative Case Study - Sakti, Syahria Anggito; Suminar, Yulian Agus Suminar; Kurniawan, Arifin Teguh (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2026)
This qualitative case study examined how Tabayyun was introduced and internalized as a form of digital-ethical guidance for young children encountering aggressive, confusing, or misleading digital content. The study involved nine children aged five to six years, nine parents or primary caregivers, and three classroom teachers from three Islamic kindergartens in Yogyakarta, Indonesia. Participants were selected purposively based on children’s regular digital-device use and observable digitally mediated aggressive responses. Data were collected over three months through 36 naturalistic observation sessions, semi-structured interviews, and document review, and were analyzed inductively through data condensation, coding, thematic matrices, and interpretive comparison. The findings revealed three interconnected patterns. First, aggressive digital content entered children’s everyday interactions through verbal imitation, emotional spillover, and symbolic forms of peer aggression. Second, parents and teachers translated Tabayyun into developmentally accessible practices of pausing, asking, checking, explaining, and seeking adult confirmation. Third, several children began to demonstrate emerging reflective responses, including closing inappropriate content, questioning whether digital representations were real or edited, and consulting trusted adults before reacting. These practices were more visible when parents and teachers used consistent language and coordinated guidance across home and school. The study conceptualizes these processes as Tabayyun-based digital scaffolding, a culturally situated extension of critical digital literacy that connects verification with emotional restraint, relational responsibility, and adult-supported reflection. Educational institutions may incorporate these practices into school culture, teacher guidance, parental engagement, and home-school communication. The findings remain context-specific and do not establish causal effectiveness or long-term behavioural change.